PERLAKUAN AKUNTANSI TERHADAP PEMBIAYAAN MURABAHAH - Agustinar Agustinar (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2021)
This research was also conducted in order to obtain answers to the problem